The Maluti Mystery revisited: Taxonomy of African River Frogs (Pyxicephalidae, Amietia) on the Drakensberg Mountains in southern Africa - Channing, Alan (Zootaxa, 2015)
The taxonomy of two similar frogs from the top of the Drakensberg escarpment, the Maluti River Frog and the Phofung River Frog is not settled. I examine the relevant types and type descriptions, and discover a number of errors in the literature. Some of the recent taxonomic changes were found to be unsupported. The Maluti River Frog is assigned to Amietia vertebralis (Hewitt, 1927), and the Phofung River Frog to Amietia hymenopus (Boulenger, 1920).